2018
DOI: 10.3390/app8020205
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Magnetic Properties of Ce2Fe14B Modified by Al, Ni, or Si

Abstract: Featured Application: This is a contribution towards developing low-cost Fe-based permanent magnets that are suitable for the automobile industry.Abstract: Intrinsic magnetic properties (saturation magnetization, anisotropy fields, and Curie temperatures) of Ce 2 Fe 14 B doped with Al, Ni, and Si are presented. Substitution for Fe by these elements leads to the formation of solid solutions that crystallize in the tetragonal Nd 2 Fe 14 B structure. Substituting Al, Ni, or Si for Fe leads to a decrease in both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This value is observed to be around 5% greater than the 931.1 kA/m reported by Herbst et al [3] for Ce 2 Fe 14 B at 22°C. Such a difference may be due to the contribution of secondary phases such as α-Fe, which is also observed by Kayode et al [17]. The H a of dopant-free Ce 2 Fe 14 B is measured as 28.1 kOe which is 8% higher than the 26.0 kOe value reported in the literature [20][21].…”
Section: Accepted Manuscriptmentioning
confidence: 48%
“…This value is observed to be around 5% greater than the 931.1 kA/m reported by Herbst et al [3] for Ce 2 Fe 14 B at 22°C. Such a difference may be due to the contribution of secondary phases such as α-Fe, which is also observed by Kayode et al [17]. The H a of dopant-free Ce 2 Fe 14 B is measured as 28.1 kOe which is 8% higher than the 26.0 kOe value reported in the literature [20][21].…”
Section: Accepted Manuscriptmentioning
confidence: 48%
“…With 0.6 at % Si, the Curie temperature rises by 30°C [151]. Li et al [152] found in their early work that addition of 1 at% Si in (NdCe)(FeSi)B alloys improves the coercivity.…”
Section: Si and Al Additionmentioning
confidence: 99%
“…One approach for plugging the gap between ferrites and NdFeB is to replace Nd with less expensive elements. Ce-substituted NdFeB and SmCo compounds and their alloys have been investigated [31] and show promising cost-to-performance results. Ce is regarded as an RE metal but is still relatively abundant, making up 66 ppm of the earth's crust, comparing to 41 ppm for Nd [32].…”
Section: Materials That Could Be Used In Future Electrical Machinesmentioning
confidence: 99%